Pulsed electric field based cyclic protein extraction of microalgae towards closed-loop biorefinery concepts. (November 2019) - Buchmann, Leandro; Brändle, Ivraina; Haberkorn, Iris; Hiestand, Michèle; Mathys, Alexander
Graphical abstract: Highlights: Increased protein extraction with increasing electric field strength. Up to 96% free available protein extraction after PEF processing. Free protein extraction up to 29% without impeding cell growth. PEF-assisted extraction efficiency depends on the cell growth phase. Protein extraction by PEF is mostly diffusion limited. Abstract: Microalgae-based biorefinery concepts can contribute to providing sufficient resources for a growing world population. However, the performance needs to be improved, which requires innovative technologies and processes. Continuous extraction from Chlorella vulgaris cultures via pulsed electric field (PEF) processing might be a viable process to increase the performance of microalgae-based biorefinery concepts. In this study, increasing protein extraction rates were observed with increasing electric field strength, up to 96.6 ± 4.8% of the free protein in the microalgae. However, increased extraction rates negatively influenced microalgae growth after PEF treatment. A free protein extraction rate up to 29.1 ± 1.1% without a significant influence on microalgal growth after 168 h was achieved (p = 0.788). Within the scope of this work, a protocol for continuous protein extraction during microalgae cultivation by PEF processing was developed. The incorporation of innovative downstream into upstream processing could be a viable future concept.